Younger and Older Adults Weigh Multiple Cues in a Similar Manner to Generate Judgments of Learning - Hines, Jarrod C. (Neuropsychol Dev Cogn B Aging Neuropsychol Cogn, 2015)
One's memory for past test performance (MPT) is a key piece of information individuals use when deciding how to restudy material. We used a multi-trial recognition memory task to examine adult age differences in the influence of MPT (measured by actual Trial 1 memory accuracy and subjective confidence judgments, CJs) along with Trial 1 judgments of learning (JOLs), objective and participant-estimated recognition fluencies, and Trial 2 study time on Trial 2 JOLs. We found evidence of simultaneous and independent influences of multiple objective and subjective (i.e., metacognitive) cues on Trial 2 JOLs, and these relationships were highly similar for younger and older adults. Individual differences in Trial 1 recognition accuracy and CJs on Trial 2 JOLs indicate that individuals may vary in the degree to which they rely on each MPT cue when assessing subsequent memory confidence. Aging appears to spare the ability to access multiple cues when making JOLs.